PENGARUH MODUL AJAR DAN PEMBELAJARAN INTERAKTIF IPA TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Yoga Pratama; Tetty Barokah; Valina Julia Cahyani; Meideka Sapriani; Aziza Maharani; Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science education (IPA) in elementary schools plays a crucial role in shaping students' conceptual understanding and scientific thinking skills. However, the dominance of conventional teaching methods leads to low student engagement and learning outcomes. This study aims to examine the impact of using instructional modules and interactive learning on improving elementary school students' science learning outcomes. The method used is a Systematic Literature Review (SLR) of relevant articles from various scientific databases published between 2014 and 2024. The findings show that interactive instructional modules in the form of videos, educational games, digital applications, and e-books can enhance student motivation, conceptual understanding, and active participation. Modules with a contextual approach also help students connect science content with their everyday lives. The success of module implementation is highly influenced by the quality of design and teacher competence, especially in applying the Technological Pedagogical Content Knowledge (TPACK) approach and Higher Order Thinking Skills (HOTS) based learning. Challenges include limited infrastructure, teachers' insufficient understanding of differentiation, and gaps between the modules and students' characteristics. Therefore, collaboration between teachers, developers, and policymakers is necessary to support the effective implementation of interactive instructional modules.